Prenatal ultrasound diagnosis of neural tube defects in the era of intrauterine repair - Eleven years' experiences - Yu-Sin Huang; Eric C. Lussier; Ksenia Olisova; Yu-Chu Chang; Hsuan Ko; Tung-Yao Chang (Elsevier, 2021)
Objective: To modify the current neural tube defect (NTD) classification for fetal medicine specialists, and to investigate the impact of prenatal ultrasound conus medullaris position screening on the detection rate of closed spinal dysraphism and pregnancy outcomes. Materials and methods: The clinical data of 112 patients prenatally diagnosed with neural tube defects in Taiji clinic from 2008 to 2018 were retrospectively analyzed. All cases were classified following the modified classification. We compared the detection rate before and after introducing the conus medullaris screening and pregnancy outcomes for NTD types. Results: Closed spinal dysraphism type prevailed in our sample (43.8%). The median gestational age at the time of detection for cranial dysraphism was 13.3 weeks, open spinal dysraphism was 22.0 weeks, and closed spinal dysraphism was 22.6 weeks. All cranial dysraphism (n = 43) and open spinal dysraphism cases (n = 20) had pregnancies terminated. For closed spinal dysraphism Class 1, the live-birth rate was 100.0% in the cases without other anomalies and 33.3% in the cases with other anomalies, respectively (X2 = 17.25, p < 0.001). Similarly, for Class 2, pregnancy continuation rate was 50.0% in cases without other anomalies and 20.0% in cases with other anomalies, yet it failed to reach statistical significance (X2 = 0.9, p = 0.524). Conclusion: Our case series may help to improve early screening and prenatal diagnosis of NTDs. Modified classification is adjusted for use in ultrasound fetal care facilities, which could be used for predicting pregnancy outcome. We suggest promoting first-trimester anatomical screening in order to make an earlier diagnosis and therefore provide better prenatal care for open spinal dysraphism cases in the era of intrauterine repair. Our findings imply that the use of fetal conus medullaris position as a marker for closed spinal dysraphism improves the detection rate and would unlikely lead to a higher termination rate.